Design and Implementation of an EtherChannel Redundant Switched Network Using PAgP and LACP Protocols with Load‑Balancing Verification - derawi, reema; Nuredin Ahmed, (AlQalam Journal of Medical and Applied Sciences, 2025)
A company needs a dependable and quick computer network. Nevertheless, network infrastructure is a major issue that affects the network's bandwidth, yet it is frequently overlooked. EtherChannel technology can be used to resolve bandwidth problems. Using Cisco’s EtherChannel technology, the study specifically examines the use of Port Aggregation Protocol (PAgP) and Link Aggregation Control Protocol (LACP) to build redundant switched networks. The study confirms the efficiency of load balancing across aggregated links by implementing PAgP and LACP in Layer 2 trunk configurations between distribution and access layer switches. The findings demonstrate how EtherChannel ensures optimal utilization by distributing traffic evenly across several links, improving network performance, fault tolerance, and reliability. The study concludes with a comparison of PAgP and LACP, highlighting the benefits of each in various network environments and outlining potential directions for further research on load balancing and network scalability.